Transcatheter Aortic Valve Replacement in a Sinus of Valsalva Aneurysm: The Evolving Role of Structural Cardiac Imaging. (September 2019) - Rout, Amit; Madianos, Evan F.; Pfeffer, Brad J.; Damluji, Abdulla A.
Abstract : Supplemental Digital Content is available in the text.